2018
DOI: 10.1097/cnd.0000000000000208
|View full text |Cite
|
Sign up to set email alerts
|

Case of Anti–Single Recognition Particle–Mediated Necrotizing Myopathy After Influenza Vaccination

Abstract: Immune-mediated necrotizing myopathy is a very rare inflammatory disease affecting skeletal muscles. Immune-mediated necrotizing myopathy may be associated with myositis-specific autoantibodies including anti-single recognition particle and anti-3-hydroxy-3- methylglutaryl-coenzyme A reductase, infectious agents (HIV or hepatitis C), other connective tissue disorders (such as scleroderma), and malignancy. We reported a 28-year-old healthy woman presented with subacute onset ascending muscle weakness 2 weeks af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Of the 12 articles selected, clinical data were extracted for 34 patients with IMNM meeting the inclusion criteria. 7,10,[16][17][18][19][20][21][22][23][24][25] The general features, clinical manifestations, laboratory data, treatments regimen, and outcomes are shown in Tables 1 and 2. With regard to RTX efficacy, 61.8% (21/34) of patients presented a response to RTX.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 12 articles selected, clinical data were extracted for 34 patients with IMNM meeting the inclusion criteria. 7,10,[16][17][18][19][20][21][22][23][24][25] The general features, clinical manifestations, laboratory data, treatments regimen, and outcomes are shown in Tables 1 and 2. With regard to RTX efficacy, 61.8% (21/34) of patients presented a response to RTX.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the role of RTX in IMNM had been increasingly assessed in isolated case reports and small series. 7,10,[16][17][18][19][20][21][22][23][24][25] Therefore, we performed a systematic review to evaluate the efficacy and safety of RTX in the treatment of IMNM.…”
Section: Introductionmentioning
confidence: 99%
“…Prior infection (most commonly viral infection) or vaccinations (usually influenza vaccination) were also noted in more than 20% of patients with idiopathic inflammatory myopathies (Limaye et al, 2017). A woman was recently reported to have developed anti-SRP-positive IMNM two weeks after being administered influenza vaccination (Mamarabadi et al, 2018). In this case, the disease process and immune response against the influenza A (H3N2) virus may have induced the production of anti-SRP antibodies and worsened her myositis.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we reviewed all B-cell therapies for IMNM, and only RTX was identified to be effective (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(18)(19)(20)(21). B-cell depletion therapy with RTX in anti-SRP IMNM is commonly effective.…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports, anti-B-cell therapy, especially rituximab (RTX), an anti-monoclonal CD20 antibody, has been used in IMNM (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). In some cases, patients benefited from RTX, while in other cases, patients showed poor response or died from complications, such as infection (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%